Revealing Diasporic Characters through Setting in Elaine Chew’s “The Heartsick Diaspora” (2019) - Dian Ari Safitri; Safira Nur Fitriani; Nur Alifia Putri Saptiadi; Ulya Raisya Puti; Rahayu Kurnia Dewi; Aini Salsabila (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2023)
Elaine Chew exposes the impact of diaspora, dimensions of human mobility, and connectivity, in “The Heartsick Diaspora” (2019). It is about an ethnic writing group of mixed-Asian blood in London. The striking cultural differences between their native culture (Eastern) and foreign culture (Western) significantly affect the characters in the story. This study belongs to literary criticism using a formalism approach to analyze the diasporic phenomenon in the literary work. It explores the connection between the settings and qualities of the two characters in the story, namely Chandra and Wei. Chandra's personality is different from the typical Asian woman because she is cynical, often dresses androgynous, and upholds individual freedom. On the other hand, Wei, a new member of the ethnic group, seems to hide his sexual orientation from the group because it considers immoral in Eastern culture. Eventually, Elaine Chew portrays the influence of the diaspora which affects the characterization of someone because they have to adapt to their new environment but also cannot be completely separated from their roots.